Long‐term outcome after COVID‐19 infection in multiple sclerosis: A nation‐wide multicenter matched‐control study. (8th July 2022) - Bsteh, Gabriel; Assar, Hamid; Gradl, Christiane; Heschl, Bettina; Hiller, Maria‐Sophie; Krajnc, Nik; Di Pauli, Franziska; Hegen, Harald; Traxler, Gerhard; Leutmezer, Fritz; Wipfler, Peter; Zulehner, Gudrun; et al.
Abstract: Background and purpose: Long‐term outcome after COVID‐19 in patients with multiple sclerosis (pwMS) has scarcely been studied, and controlled data are lacking. The objective of this study was to compare long‐term outcome after COVID‐19 in pwMS to a matched control group of pwMS without COVID‐19. Methods: We included pwMS with polymerase chain reaction‐confirmed diagnosis of COVID‐19 and ≥6 months of follow‐up and, as a control group, pwMS matched 1:1 for age, sex, disability level, and disease‐modifying treatment type. Results: Of 211 pwMS with COVID‐19 (mean age = 42.6 years [SD = 12.2], 69% female, median Expanded Disability Status Scale = 1.5 [range = 0–7.5], 16% anti‐CD20), 90.5% initially had a mild COVID‐19 course. At follow‐up, 70% had recovered completely 3 months (M3) after COVID‐19, 83% after 6 months (M6), and 94% after 12 months (M12). Mild initial COVID‐19 course was the only significant predictor of complete recovery (odds ratio [OR] = 10.5, p < 0.001). The most frequent residual symptoms were fatigue (M3: 18.5%, M6: 13.7%, M12: 7.3%), hyposmia (M3: 13.7%, M6: 5.2%, M12: 1.7%), and dyspnea (M3: 7.1%, M6: 6.6%, M12: 2.8%). Compared to matched controls, fatigue, hyposmia, and dyspnea were significantly more frequent at M3 and still slightly more frequent at M6, whereas there was no difference at M12. pwMS with COVID‐19 had neither a significantly increased risk for relapses (OR = 1.1, p = 0.70) nor disability worsening (OR = 0.96, p = 0.60). Conclusions: Long‐term outcome of COVID‐19 is favorable in a large majority of pwMS, with only a small proportion of patients suffering from persistent symptoms usually resolving after 3–6 months. COVID‐19 is not associated with increased risk of relapse or disability. Abstract : In a nation‐wide multicenter cohort of 211 patients with multiple sclerosis (pwMS) surviving COVID‐19, 70% had recovered completely 3 months (M3) after COVID‐19, 83% after 6 months (M6), and 94% after 12 months (M12). Compared to a matched control group of pwMS without COVID‐19, residual symptoms (fatigue, hyposmia, and dyspnea) were significantly more frequent at M3 and still slightly more frequent at M6, whereas there was no difference at M12. pwMS with COVID‐19 had neither a significantly increased risk for relapses nor disability worsening.